SBAS-derived TEC maps: a new tool to forecast the spatial maps of maximum probable scintillation index over India - Sunda, Surendra; Yadav, Sneha; Sridharan, R.; Bagiya, Mala S. (My University, 2017)
With the increase in the use of satellite-based navigation services, the forecasting of L band scintillation has turned out to be of paramount importance as it affects their accuracy and availability. Forecasting the time of occurrence or non-occurrence, strength and probable location of scintillation enables the service providers and users to take appropriate action to mitigate the effects and optimize the services. We use the recently developed method to retrieve TEC from the ionospheric correction data transmitted by the Indian satellite-based augmentation system (SBAS)–GAGAN. By making use of the established linear relation between the dusk time TEC and the maximum probable scintillation intensity (S4max), scintillation forecast maps have been generated as early as 1930 LT. The superposition of actual S4 measurements, obtained from the GAGAN network of receivers, on the forecasted S4max map shows that the actual measurements are less than the predicted S4max except on very fewoccasions. The potential of the simple technique to predict the 2 D maps of maximum probable scintillation index for the whole night has been demonstrated which with more refinements could evolve into a viable forecast or forewarning system.
Keywords: TEC; EIA region; Amplitude scintillation S4; Satellite-based augmentation system; GAGAN